90-Gene Expression Profiling for Tissue Origin Diagnosis of Cancer of Unknown Primary - Zhang, Yi; Xia, Lei; Ma, Dawei; Wu, Jing; Xu, Xinyu; Xu, Youtao (Frontiers in Oncology, 2021)
Cancer of unknown primary (CUP), in which metastatic diseases exist without an identifiable primary location, accounts for about 3–5% of all cancer diagnoses. Successful diagnosis and treatment of such patients is difficult. This study aimed to assess the expression characteristics of 90 genes as a method of identifying the primary site from CUP samples. We validated a 90-gene expression analysis and explored its potential diagnostic utility in 44 patients at Jiangsu Oncology Hospital. For each specimen, the expression of 90 tumor-specific genes in malignant tumors was analyzed, and similarity scores were obtained. The types of malignant tumors predicted were compared with the reference diagnosis to calculate the accuracy. In addition, we verified the consistency of the expression profiles of the 90 genes in CUP secondary malignancies and metastatic malignancies in The Cancer Genome Atlas. We also reported a detailed description of the next-generation coding sequences for CUP patients. For each clinical medical specimen collected, the type of malignant tumor predicted and analyzed by the 90-gene expression test was compared with its reference diagnosis, and the overall accuracy was 95.4 %. In addition, the 90-gene expression profile generally accurately classified CUP into the cluster of its primary tumor. Sequencing of the exome transcriptome containing 556 high-frequency gene mutation oncogenes was not significantly related to the 90 genes analysis. Our results demonstrate that the expression characteristics of these 90 genes can be used as a powerful tool to accurately identify the primary sites of CUP. In the future, the inclusion of 90-gene expression testing in pathological diagnosis will help oncologists use precise treatments, thereby improving the care and outcomes of CUP patients.